Employment Protection and Firm-Provided Training: Quasi-Experimental Evidence from a Labour Market Reform - Massimiliano Bratti; Maurizio Conti; Giovanni Sulis (Institute of Labor Economics (IZA), 2019)
In 2012, a labour market reform in Italy known as the Fornero Law substantially reduced firing restrictions for open-ended contracts in the case of firms with more than 15 employees. The results from a difference in regression discontinuities design that compares firms below versus those above the cut-off before and after the reform demonstrate that after the Fornero Law was introduced, the number of trained workers increased in firms just above the threshold, with an order of magnitude of approximately 1.5 additional workers in our preferred empirical specification. We show that this effect might be partly explained by the reduction in worker turnover and a lower use of temporary contracts at the threshold after the reform. Our study highlights the potentially adverse effects of employment protection legislation (EPL) on training in dual labour markets due to larger firms seeking to avoid the higher costs of EPL via temporary contracts.
Keywords: J42; J63; J65; M53; 330; employment protection legislation; training; dual labour markets; temporary contracts; Italy